Efeito de herbicidas sobre a densidade populacional de Pratylenchus brachyurus em cultivares de soja - Macedo, Leonardo Barros de (2012)
Soybean (Glycine max L.) is now a major export products from Brazil and one of the main commodities in the world. In the Central West region of Brazil, the main soybean-producing region, the lesion nematode, Pratylenchus brachyurus, has become a major problem for culture can lead to significant losses. Weeds are also a limiting factor for obtaining high yields in soybean, and herbicide application to control it can affect the population of nematodes. This study aimed to evaluate the effect of herbicides, including glyphosate, on the population density of P. brachyurus on soybean conventional and transgenic cultivar. Two experiments were conducted in field conditions and another in a greenhouse in 2010/2011 harvest. The experimental design of the first was completely randomized in factorial arrangement 2x4+2, with four replicates. In greenhouse the design was completely randomized, with the same factorial design and six replications. The factors of the treatments consisted of cultivars, with two levels (BRSGO Iara and M-SOY 8001), and methods of weed control, with four levels (pull-off manual and chemical control with lactofen, chlorimuron-ethyl, and haloxifop-r). Two additional treatments consisted of transgenic cultivar BRS Valiosa RR with manual control of weeds and glyphosate. The assessments for the population of P. brachyurus, in the field were made at 45 and 90 days after emergence (DAE). We also evaluated the biomass, leaf area index (LAI), fresh and dry mass of pods. In the greenhouse were measured wet weight of roots and aboveground biomass at 30 and 60 DAI. The reproduction factor (RF) was determined in both trials. In the field, to calculate the RF was considered the population of nematodes 45 DAE as initial population. The use of transgenic cultivar and glyphosate did not affect the population density of P. brachyurus. There was no difference in the behavior of cultivars in relation to nematode P. brachyurus. Herbicides clorimuron, lactofen and haloxifop also did not affect the population of P. brachyurus. However clorimuron and lactofen reduced the growing of soybean cultivars BRS Iara and M-SOY 8001.